2022
DOI: 10.1007/s11356-022-23857-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of local government competition and green technology innovation on economic low-carbon transition: new insights from China

Abstract: The government-led Chinese economic development system determines that local government competition is a significant factor affecting the economic low-carbon transition. Driving an economic development mode with green technology innovation as the core is the critical path to realizing an economic low-carbon transition. Consequently, it is of significant practical relevance to investigate the impact of local government competition and green technology innovation on the economic low-carbon transition under the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 89 publications
1
15
0
Order By: Relevance
“…China is facing several challenges in its efforts to achieve technological innovation and enhance R&D achievements. Among these obstacles are issues such as low conversion rates of R&D achievements, a disconnect between the innovation chain and industrial chain and insufficient independent innovation momentum (Xu et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…China is facing several challenges in its efforts to achieve technological innovation and enhance R&D achievements. Among these obstacles are issues such as low conversion rates of R&D achievements, a disconnect between the innovation chain and industrial chain and insufficient independent innovation momentum (Xu et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Green initiatives have less of an impact on the environment, and it's cheaper to nance enterprises that use GTI because of government incentives like incubation, guarantees, rate of interest subsidies, etc (Mansour, 2023). The study (Xu et al, 2023) employs panel threshold modeling, the generalized system method of moments, and geographically weighted regression to systematically investigate the relationship among innovative green technology and the nancial impact of the environmental friendly transition from the perspective of local government struggle. The ndings show that developing of green technologies considerably aids the transition to a low-carbon economy.…”
Section: H6 Gti Mediates the Association Among Gf And Social Sustaina...mentioning
confidence: 99%
“…In addition, capital flows were also found to be an important mechanism by which government tax competition affects sustainable development [13]. Xu et al (2023) argued that government competition not only directly inhibits low-carbon development, but also reduces the role of green technological innovations as a driver of low-carbon transitions [14]. Nonetheless, some scholars have found that local adoption of tax competition can also be advantageous in mitigating CE.…”
Section: Literature Reviewmentioning
confidence: 99%